Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan BUMN PT. Kimia Farma (Persero) Tbk Periode 2012-2014 - LUDISRI, AFTI; , Dra. Chuzaimah, M.M (2017)
The purpose of this thesis is to learn how the financial performance of the Kimia Farma (Persero) Tbk in terms of financial ratio analysis the period from 2012-2014 by the Minister of State-Owned Enterprises No:KEP-100/MBU/2002. Kimia Farma (Persero) Tbk as one of the largest pharmaceutical companies in Indonesia. Data were analyzed financial statements consisting of balance sheet and income statement 2012-2014. The method of data analysis is descriptive analysis. From the company's financial statement are analyzed by ratio of profitability, liquidity, activity and solvability. The results showed that the assessment of financial performance Kimia Farma (Persero) Tbk 2012-2014 showed a healthy predicate with the AA category.